Gynecological Evaluation of Benign Ovarian Cysts, Association with Menstrual Irregularities and Reproductive Health in Women. A Clinical Study - Shazia Ashraf, Nosheen Sikandar Baloch, Lubna Aslam, Hanana Hameed, Varsha Kumar, Summan Farooq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Benign ovarian cysts are a common gynecological condition among women of reproductive age and are frequently associated with menstrual irregularities and adverse effects on reproductive health. Aim and Objectives: This study aimed to evaluate the prevalence and types of benign ovarian cysts in women aged 20 to 45 years and to investigate their association with menstrual irregularities and reproductive health outcomes, with a particular focus on the clinical spectrum of endometrioma syndrome. Methodology: A clinical observational study was conducted involving 89 premenopausal women aged 20–45 years diagnosed with benign ovarian cysts. Each participant underwent a comprehensive gynecological evaluation, including detailed history-taking, pelvic examination, transvaginal ultrasonography, and hormonal profiling. Data on menstrual patterns, reproductive history, and associated symptoms were collected and analyzed using appropriate biostatistical models. Results: Of the 89 patients, 64% presented with menstrual irregularities, such as oligomenorrhea, menorrhagia, and dysmenorrhea. Functional cysts were the most prevalent (37.1%), followed by serous cystadenomas (20.2%) and dermoid cysts (15.7%). Endometriomas accounted for 14.6% of cases and were significantly associated with menstrual irregularities (84.6%), infertility (69.2%), and severe dysmenorrhea (92.3%). Women with endometriomas were more likely to be over the age of 35 and had a longer duration of symptoms. Conclusion: Although less common, endometriomas impose the highest clinical burden among benign ovarian cysts due to their strong association with menstrual disturbances, infertility, and chronic pelvic pain. Early identification and tailored management strategies are essential to improve reproductive outcomes and enhance quality of life in affected women. Keywords: Ovarian Cysts, Endometrioma, Infertility, Dysmenorrhea, Menstruation, Ultrasound, Reproduction